P-201 Strategic success of a whole system approach to end of life care. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Sevant, Debbie
Abstract : Context: A system wide review of end of life care services identified a number of gaps in service provision. A Hospice Enhanced End of Life Care project was commissioned to; Extend availability of hospice advice line from 8 to 8, 7 days a week. An enhanced hospice at home (H@H) service including: An increase in availability of H@H within the community/care homes from 8 to 8, 7 days a week; Introduction of community rapid response service 8 to 8, 7 days a week; Introduction of a specialist palliative care In–Reach Service to coordinate rapid end of life care discharges from hospital. Key achievements: Service user feedback: ' Without your help and support my husband would have died in hospital. You provided and arranged rapid discharge so my husband could come home. We are very grateful for everything you have done. ' Professional's feedback-' Very friendly, helpful and quick to respond. Had very good feedback from patients and relatives. Have really helped make getting patients where they want to be so much easier and quicker which is greatly appreciated.' Referrals increased by 24.09% (target 9%); Calls to the hospice advice line increased by 23% (target 17%); Preferred place of death achieved 100% to 88% (the target was 88% and in some months the target was over achieved and met up to 100%); Increase in hospital ward referrals, improving time taken from referral to assessment by less than 24hours in most cases; Average 25 referrals monthly; The average 24–hour response time increased by 23%. Key strategic success: Demonstrated impact of a whole systems approach to end of life care; Working in partnership with local hospital, community providers and Clinical Commissioning Group; Raised the profile of end of life care within the acute setting; Relationship building between partners creating a 'bridge' engendering a genuine 'can do attitude'; Fast track provision appropriately targeted with a regular review of the patient's needs to optimise the use of resources; Allows a more flexible delivery of individualised care according to changing needs for people.